Leadership Empowerment Values: A Literature Review - Eric Hermawan; Antaiwan Bowo Prayogno; Antoni Ludfi Arifin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this article is to conduct a literature review related to leadership empowerment viewed from 6 values, namely integrity, collaboration, agility, dedication, innovation and meaningfulness. This study is a literature review of related journals. The literature was collected from 50 journal articles from 2000 to 2021. Based on the results of the review, it is known that the value of integrity in leadership empowerment refers to honesty and consistency between values and behaviors adopted. Collaborative leadership empowerment is needed to foster an environment that supports collaboration at work. Agility in leadership is demonstrated through flexible leadership and can lift the capabilities of the staff, so that they can contribute to the development of the company in a more advanced direction. Dedicated leaders work selflessly, have confidence in what they are doing, the goals they want to achieve, and how to get there. Innovative leaders are leaders who are willing to learn and change, willing to invest in learning and changing existing mindsets of individuals, teams and organizations. Meaningful leadership is characterized by leadership that has quality intellectual, social and moral abilities and has a positive effect on employee work. In short, these six values contribute effectively towards the quality of good leaders.